Dramatic changes in muscle contractile and structural properties after 2 botulinum toxin injections - Minamoto, Viviane B.; Suzuki, Kentaro P.; Bremner, Shannon N.; Lieber, Richard L.; Ward, Samuel R. (Muscle & nerve, 2015)
ABSTRACT Introduction: Botulinum toxin is frequently administered serially to maintain therapeutic muscle paralysis, but the effect of repeated doses on muscle function are largely unknown. This study characterized the muscle response to 2 onabotulinum toxin (BoNT) injections separated by 3 months. Methods: Animal subjects received a single toxin injection (n = 8), 2 BoNT injections separated by 3 months (n = 14), or 1 BoNT and 1 saline injection separated by 3 months (n = 8). Results: The functional effect of 2 serial injections was exponentially greater than the effect of a single injection. While both groups treated with a single BoNT injection had decreased torque in the injected leg by approximately 50% relative to contralateral legs, the double BoNT injected group had decreased torque by over 95% relative to the preinjection level. Both single and double BoNT injections produced clear signs of fiber‐type grouping. Conclusions: These experiments demonstrate a disproportionately greater effect of repeated BoNT injections. Muscle Nerve 52: 649–657, 2015